RELASI INTELEKTUAL MINANGKABAU DENGAN MESIR AWAL ABAD XX - Fitri, Rahmi Nur (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2021)
Abstract: Egypt was the initiator of modernist Islam in the early twentieth century. The euphoria of this wave got to Minangkabau. The alteration center of Islamic studies had shifted the interest of previously oriented to Mecca. This process of gradual displacement increased interrelational thought strongly. Social interaction and various similarities in facing the West as a challenges fostered the spirit of Islamic revitaliton which came from Egypt. The awakening flowed into Minang lands. The offering of the concepts of Egyptian modernism then aroused the fire of modernization of intellectualism in Minangkabau. In addition, in the early twentieth century, Minangkabau youth dominated the number of students from Dutch East Indies. Majority of them became reformers upon their return to Minangkabau.Abstrak: Mesir adalah penggagas Islam modernis pada awal abad ke-20. Euforia gelombang ini sampai ke Minangkabau. Perubahan pusat studi Islam telah menggeser minat yang sebelumnya berorientasi ke Mekkah. Proses perpindahan bertahap ini meningkatkan pemikiran interrelasional dengan kuat. Interaksi sosial dan berbagai kesamaan dalam menghadapi Barat sebagai tantangan menumbuhkan semangat revitalisasi Islam yang datang dari Mesir. Kebangkitan mengalir ke tanah Minang. Tawaran konsep-konsep modernisme Mesir kemudian membangkitkan api modernisasi intelektualisme di Minangkabau. Selain itu, pada awal abad ke-20, pemuda Minangkabau mendominasi jumlah pelajar dari Hindia Belanda. Sebagian besar dari mereka menjadi reformis sekembalinya mereka ke Minangkabau.